Republic of North Macedonia : Central Bank Transparency Code Review. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The National Bank of the Republic of North Macedonia (NBRNM) is implementing advanced transparency practices. The long-standing commitment to transparency noted by a number of stakeholders and forcefully re-affirmed in the recent period is well anchored in the law, and it has been designated by the NBRNM as a strategic objective to fulfill its mandate. This policy has earned the NBRNM noteworthy trust from stakeholders met by the mission, and it has paid significant dividends in terms of anchoring its autonomy and ensuring policy effectiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy